SISTEM INFORMASI SIMPANAN ANGGOTA KOPERASI MANUNGGAL PERKASA KABUPATEN CIREBON BERBASIS WEB - Ernawati Ernawati; Deny martha; Agus Sevtiana (Universitas Catur Insan Cendekia (CIC) Cirebon, 2017)
Abstract The development of Information Technology has spread to different areas of the current effort. With this, one person can communicate from one place to another. The selected method varied. One of them is a Web-based Information Technology. The Website has its advantages and strengths in terms of promotion and introduce various things to the community. Cooperatif employee Koperasi Manunggal Perkasa (KMP) Kabupaten Cirebon is under the auspices of the PT. Indocement Tunggal Prakarsa, Tbk Cirebon is a business entity engaged in the loan and save Middle-Small business. Along with increasing members in KMP, the data processed storedincrease too. KMP shall have Information Systems to facilitate the processing of data and information. In this research, the author will create a web-based Information System for the member’s deposits. The Website will be created using some software, that is HTML, Macromedia Dreamweaver MX, Adobe Photoshop, PHP and MySql for storage media database so that data can be securely stored and can be changed at any time. On the main website has information contents about Koperasi Manunggal Perkasa and on the system website has transaction entry data of the member’s deposits. This system has access for the members to view deposit data using internet network. Keywords: System, Information, Cooperative, Deposit, Website.